"Suffer Not the Evil One": Unitarianism and the 1826 Maryland Jew Bill. (13th August 2020) - Eisner, Eric
Abstract : The 1826 Maryland Jew Bill was the most protracted and heated fight over Jewish political rights in the United States. For eight years, in the legislature, in newspapers, and in elections, Marylanders debated whether Jews should be allowed to hold government office or positions of public trust, a struggle that garnered journalistic coverage from throughout the country. Historians have not explained why Maryland, a state with very few Jews in the early nineteenth century, was the site of the country's largest debate over their legal status. This study argues that Unitarianism, which did not claim many adherents in Maryland at the time of the Jew Bill but occupied an outsized role in the state's debates about religious rights and Christian orthodoxy, is a key part of the story of Jewish rights in Maryland; the state's unique experience with Unitarianism is one of the causes of the state's unique place in the story of Jewish rights in the United States.